2023
DOI: 10.1002/cam4.5774
|View full text |Cite
|
Sign up to set email alerts
|

NSD3, a member of nuclear receptor‐binding SET domain family, is a potential prognostic biomarker for pancreatic cancer

Abstract: Background Members of the nuclear receptor‐binding SET domain (NSD) family of histone H3 lysine 36 methyltransferases comprise NSD1, NSD2 (MMSET/WHSC1), and NSD3 (Wolf–Hirschhorn syndrome candidate 1‐like 1, WHSC1L1). While the expression of NSD genes is essential to normal biological processes and cancer, knowledge of their expression levels to prognosticate in cancer remains unclear. Methods We analyzed the expression patterns for NSD family genes across multiple cancer types and examined their association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…In breast cancer, increased expression of NSD3 correlated with a decrease CD8+ T cells and increased PD-L1 gene [65], in agreement with Xu et al in lung cancer. In contrast, in PAAD, through bioinformatic studies, upregulation of NSD3 correlated with increased immune infiltration, specifically macrophages, B cells, neutrophils, CD8+ T cells and dendritic cells [47]. Taken together, there is evidence linking the role of NSD3 in IFN response and immune modulation, however, further studies are needed to accurately state the function.…”
Section: Ifn Pathwaymentioning
confidence: 93%
See 2 more Smart Citations
“…In breast cancer, increased expression of NSD3 correlated with a decrease CD8+ T cells and increased PD-L1 gene [65], in agreement with Xu et al in lung cancer. In contrast, in PAAD, through bioinformatic studies, upregulation of NSD3 correlated with increased immune infiltration, specifically macrophages, B cells, neutrophils, CD8+ T cells and dendritic cells [47]. Taken together, there is evidence linking the role of NSD3 in IFN response and immune modulation, however, further studies are needed to accurately state the function.…”
Section: Ifn Pathwaymentioning
confidence: 93%
“…A study in colorectal cancer (CRC) cells showed that overexpression of NSD3 increased phosphorylation of ERK leading to an enhancement of proliferation and migration of CRC cells [60]. Xiong et al, on pancreatic cancer cells, also found a correlation on a decrease of EGFR/ERK pathway activation with NSD3 knockdown [47].…”
Section: Egfr Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Xiong et al described a variety of NDS3 missense mutations and T419Pfs*8/Nfs*28/N mutations in four cases of stomach adenocarcinoma (STAD), two cases of colon adenocarcinoma (COAD) and single cases of breast invasive carcinoma (BRCA) and pancreatic adenocarcinoma (PAAD). Likewise, nonsense mutations in NSD3, such as, E1181K and T2342A, enhance the growth of cancer cells and xenograft tumors by disrupting an autoinhibitory loop in the NSD3 protein, thereby increasing enzymatic activity [47,48]. More studies regarding the mutations found in NSD3 are necessary to identify the significance of these mutations on cancer progression.…”
Section: Mutationsmentioning
confidence: 99%
“…A study in colorectal cancer (CRC) cells showed that overexpression of NSD3 increased phosphorylation of ERK, leading to enhanced proliferation and migration of CRC cells [60]. Xiong et al, in pancreatic cancer cells, also found a correlation between decreased EGFR/ERK pathway activation and NSD3 knockdown [47].…”
Section: Egfr Pathwaymentioning
confidence: 99%